Efficiency of a pelvic circumferential compression device for continuous hemorrhage of peripheral soft tissue of the pelvis: A case report. (June 2019) - Takeda, Shinsuke; Yoneda, Hidemasa; Tabuchi, Akihiko; Hirata, Hitoshi
Summary: Background: A pelvic circumferential compression device (PCCD) is a belt that is wrapped around a fractured pelvis and tightened with a closing mechanism. The SAM Sling® is one of the most common PCCDs used for trauma management. Although the use of the SAM Sling® for reduction and stabilization of unstable pelvic ring fracture has become the standard of care in most relevant trauma scenarios, it is not usually used for stopping continuous hemorrhage of the peripheral soft tissue of the pelvis without unstable pelvic ring fractures. Case presentation: We report the case of a 79-year-old woman with life-threatening and unexpected continuous subcutaneous and intramuscular hemorrhage of the buttocks and groin area. She did not have unstable pelvic ring fractures but had hemorrhagic shock and acute traumatic coagulopathy (ATC). By use of the SAM Sling®, the hemorrhage was controlled, and she was eventually rescued. Conclusions: We propose the use of the SAM Sling® to stop continuous bleeding in the state of ATC regardless of unstable pelvic ring fracture.